(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Micro emulsions are clear, stable, isotropic mixtures of oil, water and surfactant, frequently in combination with a co-surfactant. Micro emulsions act as potential drug carrier systems for oral, topical, and parenteral administration. They offer the advantage of spontaneous formation, ease of manufacturing and scale-up, thermodynamic stability, and improved drug solubilization and bioavailability. Knowledge of the various methods available to thoroughly characterize a microemulsion system is essential. While microemulsion is used in several fields, in this review the pharmaceutical applications are emphasized. Micro emulsions are one of the best candidates as novel drug delivery system because of their long shelf life, improved drug solubilization with ease of preparation and administration. They have emerged as novel vehicles for drug delivery which allow controlled or sustained release for ocular, percutaneous, topical, transdermal, and parenteral administration of medicaments. The main objective of this review paper is to discuss Micro emulsions as drug carrier system with other possible applications.